Size–Number and Shape Distribution of Buried Seeds in Soil in a Field Not Cultivated for More Than 10 Years - Luís Silva Dias (International Journal of Plant Biology, 2022)
Seeds act as reserves for plant dispersion in time and their burial in soil plays an essential role in preventing or reducing losses. Two hypotheses regarding the depth distribution of seeds in soil were investigated. One states that the burial of small seeds is restricted to shallower depths than large seeds. The other states that seed shape is important to burial. The fraction of seeds located at depths allowing viable non-photosynthetic growth was also investigated in relation to size and shape. Cores of 20 cm depth were taken from soil with an auger, divided in eight fractions of equal length and sorted through a series of ten sieves, and viable spherical and non-spherical seeds were separately counted. Burial was evaluated by the symmetry of depth–number distributions fitted by Weibull equations. The maximum depth for successful germination and emergence was calculated by combining Weibull equations with published or original material on the relationship between the volume and mass of seeds, and the maximum elongation of hypocotyls in soil. The burial of smaller seeds was found to be restricted to shallower depths, but in larger seeds, size itself appeared to be an unsurmountable barrier to burial. Smaller spherical seeds buried at shallower depths than smaller non-spherical seeds, their number decreasing monotonically with depth, while the number of non-spherical seeds increased from the surface to 10.0–12.5 cm, decreasing thereafter. Larger seeds, spherical or non-spherical, had essentially the same depth–number distribution. In very small seeds (≤0.014 mm3; approximately 75% of the 29,740 total seeds), almost all spherical and non-spherical seeds were at depths at which non-photosynthetic viable growth would be unsustainable. This fraction reduced as the size of seeds increased, but it never fell below 50% and was only rarely less than 80%. The implications of these high values for aboveground recruitment are discussed in terms of the density of seeds.